Promoting patient safety in critically ill patients: nursing interventions in surveillance and prevention of ocular injuries - Anabela Carvalho Raposo; Maria Candida Durao; Maria do Rosário Pinto; Helga Rafael Henriques; Joana Ferreira Teixeira (Acute and Critical Care)
Corneal surface injuries occur frequently (59.4%) in critically ill patients, and the average time for their appearance is 8 days. Such injuries are primarily related to dry eye, which increases the risk of exposure injury in patients admitted to intensive care units. This can result in a severe ulcer or perforation that results in partial to total loss of vision, decreasing the quality of the patient's life. This is a sensitive nursing care area requiring further investigation. Thus, this review aims to analyse nursing interventions that aim to prevent ocular surface injuries. An integrative literature review was carried out from May to August 2023 in the Medline, CINAHL, Scopus, Web of Science, and PubMed databases using the Whittemore and Knafl methodology. Inclusion and exclusion criteria were subsequently applied to assess the results. After verifying result eligibility, seven documents were identified for data extraction and analysis. The results suggest the importance of recognizing risk factors for ocular injuries in critically ill patients, surveillance as a nursing competency, adequate ocular hygiene and effective lubrication, and managing environmental conditions to prevent corneal injuries. Implementing surveillance and intervention protocols for critically ill patients at risk of corneal injuries requires specialized training for critical care nurses. Specifically, environmental management, including temperature and humidity control, is highlighted as an area that merits further research.